Nano Tips for Developing Magnetic Charisma with Shadé Zahrai. - Zahrai, Shadé (linkedin.com, 2022)
Get tips for navigating your personal and professional life with more charisma. Each video is less than two minutes long, so you can make learning fit into even your busiest days.